Factors affecting women's access to primary care in the United States since the Affordable Care Act: A mixed-methods systematic review. - Allison Gilchrist; Gunasekara Vidana Mestrige Chamath Fernando; Paula Holland; Faraz Ahmed (PLoS ONE)
Background In the United States, the Affordable Care Act (ACA) expanded public and private health coverage, increased health insurance affordability, reduced healthcare costs, and improved healthcare quality for many. Despite ACA provisions, lack of insurance and other factors continue to affect working-age women's access to primary care services. Methods We conducted a mixed-method systematic review to identify factors that affect women's access to primary care services since the ACA. In January 2021, MEDLINE, CINAHL, PsycINFO, and Web of Science were searched from 2010 to 2021 and an updated search was conducted in October 2023. We included 26 quantitative and qualitative studies reporting determinants, barriers and facilitators of women's primary care access for women (18 to 64 years). Studies reporting measures of potential access, such as health insurance, and measures of realized access-healthcare service utilization, were included. The Mixed-Methods Appraisal Tool (2018) was used to rate the quality of studies. Andersen's Behavioral Model of Health Services Use guided the narrative synthesis. Findings We found consistent evidence that ACA provisions expanding state Medicaid eligibility led to improved insurance coverage, especially for lower-income groups. We found mixed evidence of associations between individual-level determinants, such as age, education, race/ethnicity, income, and different measures of access. Limited qualitative evidence suggests that insurance coverage, low-cost care, positive patient-provider relationships, social support, and translation services enhance access for immigrants and refugees. Barriers include lack of coverage, high healthcare costs, culturally unresponsive healthcare services, poor patient-provider relationships, and transportation issues. Conclusion Adoption of ACA's expanded Medicaid eligibility criteria would expand insurance coverage to women living in non-expansion states. Innovative healthcare policies, programs, and interventions at the federal, state, and local levels are needed. Suggested strategies include interventions expanding primary healthcare service availability and patient navigation services, and promotion of health literacy, culturally sensitive services, and provider bias education/training.